Spidroin-Based Biomaterials in Tissue Engineering: General Approaches and Potential Stem Cell Therapies - Qi Zhang; Min Li; Wenbo Hu; Xin Wang; Jinlian Hu (Stem Cells International)
Spider silks are increasingly gaining interest for potential use as biomaterials in tissue engineering and biomedical applications. Owing to their facile and versatile processability in native and regenerated forms, they can be easily tuned via chemical synthesis or recombinant technologies to address specific issues required for applications. In the past few decades, native spider silk and recombinant silk materials have been explored for a wide range of applications due to their superior strength, toughness, and elasticity as well as biocompatibility, biodegradation, and nonimmunogenicity. Herein, we present an overview of the recent advances in spider silk protein that fabricate biomaterials for tissue engineering and regenerative medicine. Beginning with a brief description of biological and mechanical properties of spidroin-based materials and the cellular regulatory mechanism, this review summarizes various types of spidroin-based biomaterials from genetically engineered spider silks and their prospects for specific biomedical applications (e.g., lung tissue engineering, vascularization, bone and cartilage regeneration, and peripheral nerve repair), and finally, we prospected the development direction and manufacturing technology of building more refined and customized spidroin-based protein scaffolds.